THE USAGE OF MODERN TEST SYSTEMS WHILE TEACHING THE SUBJECT OF MEDICAL CHEMISTRY - Maxmudov Sulton Obit ugli, Assistant teacher of Medical chemistry department of Bukhara State Medicine Institute. (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
It is important to improve the knowledge, skills and abilities of students in the field of medicinal chemistry and to control the process. Correctly organized theoretical questions allow the use of various tools to deepen the acquired knowledge and, most importantly, to develop their personal skills. Controlling the formation of knowledge and skills in the educational process takes an important place. In particular, control has the following functions: